Empowering Teachers through the 'Bestari' Learning Community : Enhancing Pedagogical Competence at SMKN Campalagian - Masdalia Masdalia; Elpisah Elpisah; Husain Husain (International Journal of Studies in International Education, 2025)
This study aims to analyze the role of the Bestari learning community in enhancing the pedagogical competence of teachers at SMKN Campalagian, Luyo District, Polewali Mandar Regency. This qualitative research uses a descriptive approach. The subjects of the study include the head of the learning community, the school principal, two IPAS subject teachers, and two vocational subject teachers who are also members of the Bestari community. Data were collected through interviews, observations, and documentation, while data analysis involved data reduction, presentation, and conclusion drawing/verification. The results show that the Bestari learning community significantly contributes to improving teachers' pedagogical competence. Through intensive collaboration, relevant training, and deep reflection, teachers have become more confident and innovative in addressing educational challenges. Strategic solutions, such as fostering collaboration, promoting the use of technology, and strengthening the community’s role, helped overcome the challenges teachers faced in the classroom. This initiative not only bolstered teachers’ ability to design and implement effective teaching strategies but also empowered them to adapt to changes in the educational landscape, significantly improving their overall pedagogical skills.